Research into Striga dispersal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Parasitic flowering plants of the genus Striga cause extensive damage to cereal and legume crops in Africa, including maize and cowpea. Yield losses can be greater than 50'',. Both the extent and intensity of Striga damage appear to be increasing...